Current mismatch reduction in charge pumps using regulated current stealing-injecting transistors for PLLs - Mohd Khairi Zulkalnain; Yan Chiew Wong (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A charge pump for phase locked loops (PLL) with a novel current mismatch compensation technique is proposed. The proposed circuit uses a simple yet effective current stealing-injecting (CSI) technique and feedback to reduce mismatch between the negative-channel-metal-oxide (NMOS) and positive-channel-metal-oxide (PMOS) transistors. The current stealing transistor steals the current from a replica branch and mirrors it to the output where it is added to the output branch by the injecting transistor. A feedback mechanism is used to set the drain voltages of both branches to be equal and mitigate channel length modulation and ensure high accuracy. The proposed circuit was designed on Silterra 130nm technology and simulated using Cadence Spectre. The simulation results show that the proposed circuit yields a maximum of 0.107% and minimum of 0.00465% current mismatch while operating at a low supply voltage of 800mV for a range of 100mV to 700mV. The proposed design uses only one rail-to-rail op amp for compensating the mismatch and an addition of 4 transistors and utilizing 75% of the supply voltage for high voltage controlled oscillator (VCO) tuning range.